Managing Universiti Sains Malaysia Libraries 2.0: Developing Strategic Leadership values for librarians - Mohd Pisol, Ghadzali; Radia Banu Jan, Mohamad; Shahriza Fadly, Misaridin (Universiti Sains Malaysia, 2010)
International Conference On Libraries (ICOL) 2007, 31st October - 2nd November 2007 organized by Universiti Sains Malaysia (USM) with the coorperation of Librarians Association of Malaysia at Gurney Hotel, Penang.